Research of pressure influence in the gas supply system on the energy consuption level of gas devices - Pylypiv, L. D.; Maslanych І. І. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2019)
There are investigated the influence of operating pressures in the gas supply system on the level of such energy indicators as efficiency, gas flow and gas overrun by gas equipment in residential buildings. There is established a relationship between the values of operating pressures in the gas supply system and the gas consumption level of household appliances. The causes of insufficient pressure in the gas networks of settlements are analyzed in the article. There is also developed an algorithm for calculating the change in the efficiency of gas appliances depending on the operational parameters of the gas network. It has been found that the most efficient operation of gas appliances is observed at an overpressure at the inlet of gas appliances of about 1200 Pa. To ensure the required quality of natural gas combustion among consumers and minimize gas consumption there are justified the following measures in the article: coordinating a domestic regulatory framework for assessing the quality of natural gas with international norms and standards; improving the preparation of gas coming from local wells before supplying it to gas distribution networks; auditing low pressure gas pipelines and reconstructing areas affected by corrosion; ensuring standard gas pressure in the network for the normal operation of domestic gas appliances; stating quality indicators of natural gas combustion by gas sales organizations.